(untitled) (Journal of Health Sciences, 2023)
Introduction: Atopic dermatitis (AD) is a chronic relapsing inflammatory skin disorder which involves skin barrier and immune dysregulation. The management of AD involves the use of moisturizers and immunosuppressant which are only used for temporary symptom relief and may potentially harm the fetal growth. Autologous activated platelet-rich plasma (aaPRP) is a potential adjuvant treatment for symptom control in pregnant AD patient. This report examines a case of a pregnant patient with AD treated with aaPRP and the monitoring of fetal growth until birth. Case Report: A 37-year-old pregnant patient with a history of AD when in contact with latex or consumption of dairy products came to Hayandra Clinic. As she had been working as anesthesiologist continuously in contact with latex gloves, she underwent routine aaPRP therapy for 3 years and had 15 aaPRP treatments over the course of her pregnancy. The patient had lesser lesions when AD was induced, no exacerbation of symptoms during pregnancy, and the baby was healthy during pregnancy to birth. Conclusion: The use of aaPRP therapy for the management of AD may be indicated as it controls the symptoms yet is safe for the patient during pregnancy. There was also no harm effect showing on the fetal development. A larger study such as randomized controlled trial is required to evaluate our findings.